The development of tolerance among university students (Journal of the College of Basic Education, 2022)
Tolerance has importance in the life of the individual and society. If tolerance, affection and cooperation prevail between members of the same community and different societies without discrimination or preference, psychological and social stability will be the hallmark of societies, which ultimately affects the mental health of their children and provides opportunities for progress and prosperity.Tolerance is a cognitive, sentimental, and behavioral component towards the self and the other and attitudes represented in a set of knowledge, beliefs, principles, feelings and behaviors that push the owner to reconcile with himselfAnd with the other, and make him characterized by tolerance in different life situations.It is a position that is manifested in a willingness to accept different views regarding different behavior, opinion, social status, religion and moral values without approval.The objectives of the research are to identify the level of tolerance among university students, the development of tolerance among university students, and the significance of the differences in tolerance according to the gender variable.The research sample was selected by a simple, equal - Distribution method of (108) for the First and fourth stages of university students, and the researcher adopted the tolerance measure for Rokeach and it consists of (34) paragraphs and the answer to them is (always, sometimes, never) and given (3, 2), 1), respectively, the psychometric properties of the scale were extracted.The results showed that university students are characterized by a level of tolerance, and that members of the fourth stage are more tolerant than the First stage, and there are statistically significant differences according to the gender variable in favor of males, and in light of this many recommendations and proposals were presented